BEANS – distributed data analysis for numerical simulations. Issue Volume 14:Issue S351(2019) (May 2019) - Hypki, Arkadiusz; Giersz, Mirek; Askar, Abbas; Belloni, Diogo; Leveque, Agostino
Abstract: beans is a tool for distributed data analysis. It provides web and command line interface for data analysis and plotting for huge datasets. beans is written in a general form and can be used in any field of research to analyze the data. The main purpose of beans is to provide to the community a versatile tool to store, analyze and then visualize any amount of scientific data (e.g. numerical simulation, observations).